Geography, non-homotheticity, and industrialization: A quantitative analysis - Holger Breinlich; Alejandro Cu\~nat (Center for Economic Studies and ifo Institute (CESifo), 2012)
We propose a quantitative framework for the analysis of industrialization in which specialization in manufacturing or agriculture is driven by comparative advantage and non-homothetic preferences. Countries are integrated through trade but trade is not costless and geographic position matters. We use a number of analytical examples and a multi-country calibration to explain two important empirical regularities: (i) there is a strong positive cor-relation between proximity to large markets and levels of manufacturing activity; (ii) there is a positive correlation between the ratio of agricultural to manufacturing productivity and shares of manufacturing in GDP. Our calibrated model replicates these facts and also provides a better fit to cross-sectional data on manufacturing shares than frameworks which ignore the role of trade costs or non-homotheticity. We use the calibrated model to quantitatively ana-lyze the effect of increases in agricultural productivity and a further lowering of trade barriers.
Keywords: F11; F12; F14; O14; 330; industrialization; economic geography; international trade; Industrialisierung; Arbeitsteilung; Außenwirtschaft; Entfernung; Mehr-Länder-Modell; Theorie